Development of advanced cementite-free bainitic steel using Ni, Al and Cu additions – Design concept and phase transformations study - Aleksandra Królicka; Francisca Garcia Caballero; José Antonio Jimenez; Władysław Zalecki; Roman Kuziak (Journal of Materials Research and Technology, 2023)
A novel concept, consisting of the stabilization of retained austenite with Ni, Al, and Cu additions instead of using Si as the major alloying element to prevent carbide formation, is proposed to design nanocrystalline, cementite-free bainitic steels. In this work, the novel steel (wt.%) Fe-0.40C-0.50Mn-8.0Ni-2.65Al-0.8Cu was designed. Dilatometry investigations were performed to obtain the experimental CCT and TTT diagrams for this material. It was concluded that the bainitic reaction occurs between 400 and 225 °C during a transformation time ranging from 2 h to 66.5 h, respectively. An in-depth analysis performed on the resulting materials confirmed the presence of an ultrafine structure free of cementite consisting of carbon supersaturated laths of tetragonal bainitic ferrite and retained austenite with thin film and block morphologies. The use of Ni, Al and Cu as alloying elements leads to high carbon content in both populations of retained austenite, which prevents, the formation of fresh martensite during cooling to room temperature. The results of this research constitute a novel insight into the design of ultra-fine, cementite-free bainitic steels.